'Right support, right place, right time'?. (2nd May 2023) - Wright, David
Abstract : Ambassador for Paint Pots Nurseries, David Wright, considers the Government's Special Educational Needs and Disabilities (SEND) and Alternative Provision Improvement Plan and asks if it goes far enough to achieve its own aims.